2005
DOI: 10.1080/01406720500256228
|View full text |Cite
|
Sign up to set email alerts
|

Making sense of realistic word problems: portraying working class ‘failure’ on a division with remainder problem

Abstract: Children of 10-11 years of age were interviewed while undertaking a range of mathematic problems, most of which embedded mathematical operations in textually represented realistic settings. One problem, concerning a lift moving people in the morning rush, comprised a division-with-remainder problem in which children are required, conventionally, to introduce a particular realistic consideration in order to produce the 'correct' answer. Another problem was an extended version of this, requiring children to comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 16 publications
0
19
0
Order By: Relevance
“…Those who have difficulty in solving word problems often do not know how to use their reading skills and mathematical knowledge to analyse and explore the problem situation adequately. As a result, they do not succeed in formulating a correct solution plan (Cooper & Harries, 2005;Verschaffel et al, 1999).…”
Section: Introductionmentioning
confidence: 91%
“…Those who have difficulty in solving word problems often do not know how to use their reading skills and mathematical knowledge to analyse and explore the problem situation adequately. As a result, they do not succeed in formulating a correct solution plan (Cooper & Harries, 2005;Verschaffel et al, 1999).…”
Section: Introductionmentioning
confidence: 91%
“…Contrary to this, the results of this study suggest that with well-planned and effective teacher development interventions, the issue of context in mathematics teaching may play a pivotal role in the development of learners' problem-solving abilities. The test results indicated that current school instruction given for mathematical word problems is likely to develop in students a tendency to exclude real-world knowledge and/or reality in their solution processes (Cooper & Harries, 2005;Greer, 1997;Verschaffel, De Corte, Lasure, Vaerenbergh, Bogaerts, & Ratinckx, 1999).…”
Section: Reality Sense-making and Context In Word Problem-solvingmentioning
confidence: 99%
“…An archetypal meeting point for natural language processing and mathematics education is the realm of word problems [4,14,15], a realm in which mechanised mathematics assistants (MMA) are expected to play an ever more prominent role in the years to come.…”
Section: Introductionmentioning
confidence: 99%